Digital competition law in Europe a concise guide - Wiggers, Marc Ph. M. (Marc Philippe Marie), 1979- (Wolters Kluwer/Kluwer Law International, 2019)
Digital Competition Law in Europe provides concise and comprehensive coverage of the enforcement practices and policies in the field of digital competition law of six European competition authorities. The competition law landscape is changing rapidly under pressure of the development of artificial intelligence and other digital technologies. 'Digital competition', a term and concept that has risen to the forefront of competition law, may be viewed as both promising and cautionary. On the one hand, it brings the promises of increased speed, efficiency and objectivity, and, on the other, it entails potential pitfalls such as hard-to-identify pathways to unfair pricing, dominant positions and their potential abuse, restriction of choice and abuse of personal data. Accordingly, jurisdictions around the world are taking measures to deal with this phenomenon. In this concise but thoroughly researched book -- both informative and practical -- lawyers from a prominent firm with a specialised digital competition team take stock and examine the state of digital competition in the enforcement practices of six competition authorities in Europe.